Respuesta :
For this case we have the following expression:
[tex]23 \frac {1} {6} -5 \frac {6} {8} =[/tex]
We convert mixed numbers to improper fractions:
[tex]23 \frac {1} {6} = \frac {6 * 23 + 1} {6} = \frac {138 + 1} {6} = \frac {139} {6}\\5 \frac {6} {8} = \frac {8 * 5 + 6} {8} = \frac {40 + 6} {8} = \frac {46} {8} = \frac {23} {4 }[/tex]
Rewriting the expression we have:
[tex]\frac {139} {6} - \frac {23} {4} = \frac {4 * 139-6 * 23} {24} = \frac {556-138} {24} = \frac {418} { 24} = \frac {209} {12}[/tex]
Thus, the expression is simplified as:
[tex]\frac {209} {12}[/tex]
Answer:
[tex]\frac {209} {12}[/tex]
Answer:
The difference between [tex]23 \frac{1}{6}-5 \frac{6}{8}[/tex] is [tex]17 \frac{5}{12}[/tex]
Explanation:
[tex]23 \frac{1}{6}-5 \frac{6}{8}[/tex]
[tex]\frac{139}{6}-\frac{46}{8}[/tex]
Calculating,
=[tex]\frac{139}{6}-\frac{23}{4}[/tex]
taking lcm for denominator
=[tex]\frac{278-69}{12}[/tex]
= [tex]\frac{209}{12}[/tex]
converting into mixed fraction
=[tex]17 \frac{5}{12}[/tex]